Implementasi Kebijakan Penanggulangan Bencana Melalui Program Taruna Siaga Bencana (TAGANA) Masuk Sekolah di Kabupaten Sidoarjo Tahun 2023 - Putri Nilam Cahyaning Rahmadani; Muhammad Agus Muljanto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Sidoarjo Regency is listed as one of the three regions in East Jawa Province that will experience the most disasters in 2022, which could threaten the safety of its citizens, especially groups vulnerable to disasters, one of which is children. The Taruna Siaga Bencana (TAGANA) aims to provide early education to students on how deal with disaster in order to reduce the risk of disaster occurring. This research aims to determine and analyze the success of implementing TAGANA Masuk Sekolah program in Sidoarjo Regency. The research method used is descriptive qualitative. Data collection uses interviews, observation, and documentation. This research uses a policy implementation model focus according to Geoge C. Edward III which consists of (i) Communication, (ii) Resources, (iii) Disposition, (iv) Bureaucratic Structure. The technique for determining informants uses purposive sampling anda snowball sampling. The results of this research indicate that the implementation of Tagana School Entry program in Sidoarjo Regency has not been implemented wel. This is because there are still obstacles in communication and officers do not receive incentives, which can affect the success of implementing a policy.